Peran Crowdfunding dalam Mendukung Manajemen Pembiayaan Pendidikan di SDN 02 Aur Kuning - Rahmad Fuad; Hamdi Abdul Karim (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
The purpose of this study is to analyze the role of Crowdfunding in supporting education financing management at SDN 02 Aur Kuning. This research aims to evaluate the effectiveness of Crowdfunding as an alternative source of funds for schools and to identify the factors that contribute to the success of Crowdfunding campaigns in this educational environment. This research used a descriptive qualitative approach to analyze the role of Crowdfunding in supporting education financing management at SDN 02 Aur Kuning. This method was chosen because it allows researchers to gain an in-depth understanding of the phenomenon under study through the collection and analysis of non-numerical data. The results of this study show that Crowdfunding at SDN 02 Aur Kuning highlights the success in raising funds. Crowdfunding was successful for the renovation of science laboratories and scholarships for outstanding students, with substantial contributions from alumni, the community, and non-governmental organizations. Key challenges included a lack of managerial skills in managing the funds and issues of long-term funding sustainability. Success factors include active school involvement, effective communication strategies and transparency in fund management. Support from the community, alumni, and favorable regulations are also crucial in the success of Crowdfunding campaigns.